In situ formation of Ag nanoparticles in PVDF ultrafiltration membrane to mitigate organic and bacterial fouling - Li, Xin Yong; Pang, R.; Li, J.; Sun, X.; Shen, J.; Han, W.; Wang, L. (2013)
Membrane fouling remains one of the most problematic issues surrounding membrane use in water and wastewater treatment. Organic fouling and biological fouling contribute to irreversible fouling and flux decline in these processes. In this study, to obtain both organic antifouling and antibacterial properties, in situ formed Ag nanoparticles were immobilized in poly (vinylidene fluoride) (PVDF) ultrafiltration (UF) membranes, using N,N-dimethylformamide (DMF) as the reducing agent for Ag+ and solvent for PVDF polymer simultaneously. The hydrophilicity of the membrane surface was improved by the integration of Ag nanoparticles, leading to a reduction in membrane contact angle (81 to 68°) and an increase in permeate flux (36.4 to 108.6 L/m2 h). The organic antifouling and antibacterial performance of the Ag-loading membranes were evaluated by using bovine serum albumin (BSA) aqueous solution and Escherichia coli (E. coli) as model foulants, respectively. The experimental results confirm that the immobilization of Ag nanoparticles in PVDF UF membrane can mitigate the organic and biological fouling.